2022
DOI: 10.1371/journal.pone.0258355
|View full text |Cite
|
Sign up to set email alerts
|

Improved solubility and corneal permeation of PEGylated curcumin complex used for the treatment of ophthalmic bacterial infections

Abstract: Naturally occurring curcumin can be used for the treatment of corneal bacterial infections with its limitation of poor solubility. Aim of the present study was to enhance solubility and permeation of curcumin for the treatment of corneal bacterial infections. For increasing solubility, curcumin and polyethylene glycol (PEG 6000) complex (1:3) was prepared by fusion melting method. Phase solubility studies were used for the calculation of Gibbs free energy of curcumin. Central composite rotatable design (CCRD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Jss for different formulations was in the order: M4 (containing 7% PEG 400) > M2 (containing 7% PEG 400) > M1 (containing 5% PEG 400) > M3 (containing 5% PEG 400). The results indicate that using PVP and 7% PEG 400 together enhances skin permeation compared to using PVP and 5% PEG 400, which is in line with previous studies [73,74]. This improvement is attributed to the strong hydrophilic nature of PEG 400, which increases the solubilization of the drug and enhances partition to the aqueous phase [49].…”
Section: Stability Studysupporting
confidence: 89%
“…Jss for different formulations was in the order: M4 (containing 7% PEG 400) > M2 (containing 7% PEG 400) > M1 (containing 5% PEG 400) > M3 (containing 5% PEG 400). The results indicate that using PVP and 7% PEG 400 together enhances skin permeation compared to using PVP and 5% PEG 400, which is in line with previous studies [73,74]. This improvement is attributed to the strong hydrophilic nature of PEG 400, which increases the solubilization of the drug and enhances partition to the aqueous phase [49].…”
Section: Stability Studysupporting
confidence: 89%
“…The regression coefficient ( r ) and AIC values at various times PCL conc in the Higuchi model revealed that the drug release was diffusion-controlled, whereas no significant alteration was identified across all values (1) in the Weibull model. The Weibull model provided the best adjustment curve for Cu-Q-PCL-NPs because it had a higher α value and a lower AIC value , in comparison to Q-PCL-NPs. In the case of Cu-Q-PCL-NPs, the dissolution of Cu 2+ ions were high due to the low pH (5.5); therefore, the Cu-Q-PCL-NPs has a higher drug release than Q-PCL-NPs …”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of drug release from curcumin-loaded composites was studied in an aqueous PBS medium without any modification. According to the literature, the solubility of free curcumin in such medium is almost negligible (below 0.5 μg•ml −1 ), 57 such that modification of PBS medium with additives like Tween 80 and methanol is needed. 11 Here, the complexation of curcumin by its interaction with the hydrophilic carriers gives rise to an increased solubility of curcumin in pure aqueous PBS medium, as shown in the release profiles of Figure 6.…”
Section: Structural Study Of Fabrics and Compositesmentioning
confidence: 99%